Anal encirclement using polypropylene mesh for high grade complete full-thickness rectal prolapse: A case report - Yuda Handaya, Adeodatus (Int J Surg Case Rep, 2019)
INTRODUCTION: Rectal prolapse is defined as protrusion of the rectal wall outside the anus caused by pelvic floor abnormalities. Operative repair is the only definitive treatment. Until now, there is no ideal surgical technique that can be used for all patients. PRESENTATION OF CASE: Here we report two cases of full-thickness rectal prolapse in elderly patients with high-risk comorbidities. A seventy and seventy-eight-year-old female patients presented with complaints of anal lumps. Their past medical history was significant for arrhythmia, hypertensive heart disease, and pneumonia. The patients then underwent surgical repair with mesh cerclage. The patients were hospitalized for three days after surgery. On days 3, 7, 14, and 6 months after surgery the patients did not complain of any recurrence nor complications. DISCUSSION: We did a modified anal encirclement surgical repair technique in managing these elderly patients with full-thickness rectal prolapse and high-risk comorbidities using mesh to prevent recurrence. CONCLUSIONS: Anal encirclement technique using mesh can be considered as an alternative procedure for the treatment of full-thickness rectal prolapse in elderly patients with high-risk comorbidities because this procedure is simple, safe, causes fewer postoperative complications, and also can prevent recurrence.